KETERBUKAAN DIRI (SELF DISCLOSURE)PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA SELAMA PANDEMI COVID-19 DI KELURAHAN REJOSARI KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Sutopo, Sasdilla Fieren Agliesta; Sutisna, Nono; Nainggolan, Atirista (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2021)
The Covid-19 pandemic period with various restrictions has made more people stay at home. This condition triggers new problems in the family including domestic violence. One of the vulnerable groups affected is women; meanwhile many women choose not to open themselves up to the violence they experience. Self-disclosure is a process of communication by which one person reveals information about themselve to another, which is usually hidden or confidential containing facts about the individual not known by others in the surrounding, can also be related to the situation faced and providing relevant information in the past or useful for understanding the current situation. As a result of this lack of self-disclosure, women experience a psychological burden and always get discriminatory behavior. The research aims to describe more about self-disclosure of women victims of domestic violence during Covid-19 pandemic in Rejosari Village, East SemarangSubdistrict,Semarang Regency. The research uses aqualitative approach with descriptive methods. The data collection uses an in depth interview, observation, and documentation study. The informants are determined by using purposive sampling to seven informants consisting of women victims of domestic violence, parents, health worker, and member of Integrated Service Center Seruni East Semarang Subdistrict.The result shows that self-disclosure of women victims of domestic violence during Covid-19 pandemic has been done well. After revealing self-disclosure there are problems that arise which are trauma feeling and anxiety towards domestic violence. Based on the research, the researcher proposes a program to socially assist towards the trauma feeling and anxiety of women victims of domestic violence during Covid-19 pandemic after revealing self-disclosure through Referral Service Agency Rumah Aman.The program aims to give a sense of security and reduce trauma and anxiety among women victims of domestic violence during Covid-19 pandemic after revealing self-disclosure.